Using video to support massive business courses: Learning goals and development processes - Ostashewski, N.; Hosie, Peter; Martin, Romana; Lwin, Michael (Association for the Advancement of Computing in Education (AACE), Chesapeake, VA, 2013)
This paper reports on two cases of developing online video resources for university students enrolled inmassive business courses. This exploratory investigation is focused on considering the design and development ofvideo resources for massive courses. Initially, the findings indicate that lecturers responsible for massive courses havesome common educational needs and goals for resource development and common approaches to developing videoresources. The study also identified that current technology available to lecturers allows them to efficiently develop andpresent targeted video materials for students taking massive courses. In practice, the goals and processes need carefulplanning, organization, and implementation to ensure the production of videos is an efficacious use of lecturer time.Future research needs to explore the types of resources developed and production time and costs required for variousvideo segment types, with student perceptions of the value added by online video segments for their learning.